The Influence of Customer Inertia Beliefs in Shaping Loyalty: Evidence from Freight Forwarding Services in Jakarta - Rr. Endang Wahyuni; Edi Abdurahman; Siti Aniisah; Refius Pradipta Setyanto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In the competitive freight forwarding industry, retaining loyal customers has become a critical challenge. With increasingly intense competition in the logistics industry, understanding the determinants of customer loyalty is crucial. This study examines the mediating role of customer inertia beliefs in the relationship between logistics service quality, logistics flexibility, and customer experience on customer loyalty in freight forwarding services. This study used a quantitative approach, collecting data from 300 freight forwarding customers in Jakarta and the surrounding areas through a structured survey. The sampling technique used was Proportional Stratified Random Sampling, and data analysis was performed using the SEM-PLS 4.0 model. The results show that logistics flexibility and customer experience have a direct and significant influence on customer loyalty, while logistics service quality does not have a significant direct influence. However, logistics service quality, logistics flexibility, and customer experience are proven to have a significant influence on customer inertia beliefs. Furthermore, customer inertia beliefs act as a mediating variable in the relationship between these three factors and customer loyalty. These findings indicate that inertia beliefs play a key role in maintaining customer loyalty, even when the direct influence of several factors on loyalty is insignificant.